Metformin Use Is Associated With a Lower Incidence of Hospitalization for Atrial Fibrillation in Patients With Type 2 Diabetes Mellitus - Tseng, Chin-Hsiao (Frontiers in Medicine, 2021)
Background: The effect of metformin on the risk of atrial fibrillation (AF) requires confirmation. This retrospective cohort study compared the incidence of hospitalization for AF in ever and never users of metformin. Methods: Patients with newly diagnosed type 2 diabetes mellitus during 1999-2005 were enrolled from Taiwan’s National Health Insurance database. Analyses were conducted in both an unmatched cohort of 173398 ever users and 21666 never users and in a propensity score-matched cohort of 21662 pairs of ever and never users. They were free from a diagnosis of AF before January 1, 2006 and were followed up until December 31, 2011. Hazard ratios were estimated by Cox regression incorporated with the inverse probability of treatment weighting using the propensity score. Results: A total of 303 ever users and 86 never users in the unmatched cohort and 56 ever users and 86 never users in the matched cohort developed hospitalization for AF during follow-up. The respective incidence rates were 37.72 and 92.45 per 100,000 person-years in the unmatched cohort and were 56.98 and 92.46 per 100,000 person-years in the matched cohort. The hazard ratio for ever versus never users was 0.405 (95% confidence interval: 0.319-0.515) in the unmatched cohort and 0.617 (0.441-0.864) in the matched cohort. Hazard ratios for the tertiles of cumulative duration of metformin therapy versus never users showed a dose-response effect. The findings were consistent in sensitivity analyses. Conclusion: Metformin use is associated with a lower risk of hospitalization for AF in patients with type 2 diabetes mellitus.